THE INFLUENCE OF HUMAN RESOURCES (HR) COMPETENCIES ON VILLAGE FUND MANAGEMENT (CASE STUDY AT THE PUTERAN VILLAGE OFFICE, PAGERAGEUNG TASIKMALAYA) - Dewi, Lati Sari; Setiawan, Wahdan Budi (Yayasan Pendidikan Cahaya Budaya Indonesia, 2023)
This study aims to: 1) Competence of HR in Puteran Village, 2) Management of Puteran Village Funds, 3) Knowing the influence of HR competence on the management of Puteran Village funds.There are two variables in this study, namely the competence of human resources (X) as the independent variable and the management of village funds (Y) as the dependent variable. The method used in this research is descriptive quantitative method. The data used are primary data (observations, interviews, and questionnaires) and secondary data (library studies and documentation studies). The data analysis technique used is simple regression.Based on the results of this study, it shows that: 1) HR competence is in the very good category, namely 479) village fund management is in the very good category, namely 314) the influence of HR competence on village and village management is 0.875 which means very strong, while the coefficient of determination is 76, 6%, the remaining 23.4% is influenced by other factors.